Double-deck programming method for areal energy optimal allocation in active distribution network - Zhou, Lihua; Tan, Jiangjun; Xu, Changxiang; Huang, Jihua; Shao, Yue; Feng, Xia; Zheng, Wei; Wang, Yao (Journal of physics. Conference series, 2022)
With the problem of worldwide energy and environment become more and more serious, the method that increasing power sources and the investment of substation construction is difficult to meet the rapidly growing power demand. From the theory of comprehensive resource strategic planning and the perspective of the whole society, consider the generalized power supply such as the photovoltaic power supply and interruptible load, establish double-deck programming model for areal energy optimal allocation in active distribution network. The upper planning takes the construction of generalized power supply and the minimizing the total cost of power generation and pollution control as target, improve installed volumn of various power supplies; The lower target is minimizing the net loss, and select address and determine capacitance for generalized power supply. In result, this paper use simplex method and improving PSO algorithm to calculate it. The result of a 33 bus system’s simulation say that the method has the more obvious effect of energy conserving and emissions reducing than the traditional method.